2022
DOI: 10.1177/22125868211072932
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of guideline to improve intercultural sensitivity in cross-cultural management

Abstract: This study employed Kolb’s experiential learning cycle to investigate whether experiential learning could gain effective results via cross-cultural management theories in teaching and learning. Data from experts was collected to design a teaching program, which was then implemented with the Intercultural Senility Scale to compare between the experimental and control groups using a quasi-experiment research design. Finally, using a focus group discussion, the experts’ opinions were collected for an effective gu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Their study demonstrated that an external intervention, such as the intercultural nursing course, does not make a significant and direct contribution to intercultural sensitivity, but such an intervention is valuable to enhance students' understanding on cultural structures. In a different way, Li and Longpradit (2022) depicted a highly contributive and direct role of an external intervention, the so-called intercultural teaching program, to the enhancement of intercultural sensitivity. The possible reason seems to be central to the comprehensive and detailed design of the intervention in Li and Longpradit's (2022) study compared to that of Çingöl's et al (2021Çingöl's et al ( ) study.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their study demonstrated that an external intervention, such as the intercultural nursing course, does not make a significant and direct contribution to intercultural sensitivity, but such an intervention is valuable to enhance students' understanding on cultural structures. In a different way, Li and Longpradit (2022) depicted a highly contributive and direct role of an external intervention, the so-called intercultural teaching program, to the enhancement of intercultural sensitivity. The possible reason seems to be central to the comprehensive and detailed design of the intervention in Li and Longpradit's (2022) study compared to that of Çingöl's et al (2021Çingöl's et al ( ) study.…”
Section: Introductionmentioning
confidence: 99%
“…In a different way, Li and Longpradit (2022) depicted a highly contributive and direct role of an external intervention, the so-called intercultural teaching program, to the enhancement of intercultural sensitivity. The possible reason seems to be central to the comprehensive and detailed design of the intervention in Li and Longpradit's (2022) study compared to that of Çingöl's et al (2021Çingöl's et al ( ) study. Subsequently, Üzar-Özçetin et al (2022 sought to see the interactions of intercultural sensitivity, psychological resilience, and empathetic tendency among the teachers of Syrian refugee children.…”
Section: Introductionmentioning
confidence: 99%
“…Taking a snapshot of 2022 papers reveals the quality and depth of scholarship being published. 10 articles were published between January and April (Aatif, 2022; Cui et al, 2022; Kazuyuki, 2022; Li and Longpradit, 2022; Nicol and Bice, 2022; Sung et al, 2022; Zhang, 2022; Zhao and Ebanda de B’beri, 2022; Zheng, 2022). Following a growing pattern, these articles were submitted to IJCE from researchers and authors without prior attachment to IJCE, IOE or Tsinghua.…”
Section: A Picture Of 2022 So Farmentioning
confidence: 99%
“…The pool of studies shows a tendency toward quantitative methods, employed by 17 out of 31 studies (e.g., Aba, 2019;Li & Longpradit, 2022;. Further, it features six qualitative (e.g., Corder & U-Mackey, 2015;Dervin, 2017;Matsunaga et al, 2003) and eight multi-method approaches (e.g., Chan et al, 2018;Fakhreldin et al, 2021;Roller, 2015).…”
Section: Intercultural Competence Assessment Methodsmentioning
confidence: 99%
“…(Interactional) confidence was assessed in five papers (e.g., Aba, 2019;Kurpis & Hunter, 2016;Li & Longpradit, 2022), while empathy (e.g., Machado et al, 2016), flexibility (e.g., Fakhreldin et al, 2021), critical reflection (Chan et al, 2021), and self-reflexivity (e.g., Roller, 2015) were represented in three studies. These form a center field, as the following competencies are again represented here in isolated cases.…”
Section: Assessed Competencies After the Process Model By Deardorff (...mentioning
confidence: 99%